Analysis of the Logistics Service Provider/principal relationship: In the light of innovation as a LSP strategy - Hasna Bouchette; Mostafa Achoui; Zohra Saki; Smail Kabbaj (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
The stakeholders in logistics outsourcing are logistics service providers (LSP). The trend towards outsourcing logistics operations by manufacturers and trade companies makes these providers widely sought and recognized professionals. Motivated by a search for cost efficiency, this orientation is nowadays similar to a need to acquire skills not internally available or difficult to preserve. The construction and execution of innovative value-creating offers for companies are, therefore, at the heart of the PSL strategies. The relationship that the LSP has with its principal is central to the innovation process and determines the nature and type of the implemented innovation. In this regard, the innovation is perceived by the PSL as a means of perpetuating their relationship. An analysis of the LSP / User Logistic Services dyad (producers, distributors) seems interesting to us as it allows for emphasizing the aspects of this relationship from different angles: logistics, contractual as well as the partnership level. The first part of this paper will set up the theoretical foundations of a reflection on the PSL offer, and in particular their current practices in terms of innovation. In the second part, we explain, through an extensive review of the literature, the main theories used to study the relationship between the PSL and its principal. The work aims at presenting not only testable hypotheses on a conceptual analysis, but also theories derived from the relation LSP/Principal.
Keywords: 650; Innovation; Logistics outsourcing; LSP; Principal; Relationship